7.1k views
4 votes
42x ​5 ​​ y ​4 ​​ =(−7x ​3 ​​ y)(B)

User VIRA
by
6.0k points

1 Answer

5 votes
This is my very own step-step solution:

Step 1:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

42*x^5*y^4-((-7*x^3*y)*(b))=0
Step 2:Equation at the end of step 1 :

((42•(x5))•(y4))-((0-(7x3•y))•b) = 0

Step 3:Pulling out like terms : 42x5y4 + 7x3yb = 7x3y • (6x2y3 + b)
The correct is: 7x3y • (6x2y3 + b) = 0

Quick Side Note:
Binomial can not be factored as the difference of two perfect cubes

I hope this helps a little!

Hope you have a great day!
User David Oliver
by
5.9k points